Extracting leading indicators of bank fragility from market prices : Estonia focus - Yu-Fu Chen; Michael Funke; Kadri Männasoo (Center for Economic Studies and ifo Institute (CESifo), 2006)
Banking reform has proved to be one of the most problematic elements of economic transition in central and Eastern Europe. Therefore the paper considers the development of the Estonian banking sector and derives individual banks fragility scores during transition. To this end we use option-based tools and equity prices to estimate distance-to-default measures of banks distress probabilities. Overall, the results suggest that market indicators are moderately useful for anticipating future financial distress and rating changes in transition economies. The implication for an effective supervisory framework is to use a plurality of risk scores when assessing bank vulnerability.
Keywords: E58; E44; G21; 330; banking; financial stability; bank fragility; options; Estonia; Bankenkrise; Prognoseverfahren; Bankrisiko; Bankinsolvenz; Übergangswirtschaft; Optionspreistheorie; Schätzung; Estland